Idiopathic Moyamoya Disease Presenting as Isolated Hemichorea - Hamid, Omer Abdul; Klimo, Paul, Jr.; Choudhri, Asim F.; Shah, Namrata (Journal of Pediatric Neurology, 2021)
The study aimed to describe a case of a 7-year-old Caucasian girl who developed isolated chorea in her right upper and lower extremities progressively increasing over 2 years. This study is a case report and conducted at tertiary care center. A 7-year-old Caucasian girl who gradually developed worsening choreiform movements in her right upper and lower extremities over the course of 2 years until medical attention was sought. Literature review of children presenting with chorea as the only manifestation in moyamoya disease. A 7-year-old right-handed Caucasian girl presented with progressively worsening choreiform movements in her right upper and lower extremities affecting her fine motor skills and gait impairment There was no weakness, hyperreflexia, or spasticity on her neurological exam. Neuroimaging studies showed “ivy sign,” asymmetric prominence of vessels within the subarachnoid spaces overlying the left cerebral hemisphere with corresponding serpiginous T2 fluid-attenuated inversion recovery abnormality, but no parenchymal volume loss or diffusion restriction. Magnetic resonance angiography showed focal moderate-to-severe stenosis at the junction of the paraophthalmic and supraclinoid segments of the left internal carotid artery, with poststenotic dilatation. Angiography demonstrated focal stenosis involving the ophthalmic segment of the left internal carotid artery with 50% stenosis. There was compensation through a medium sized left posterior communicating artery as well as posterior cerebral artery to middle cerebral artery and anterior cerebral artery collateralization. Brain single-photon emission computerized tomography scan showed no evidence of perfusion defects in the cerebral hemispheres, basal ganglia, or thalami. She underwent successful revascularization procedure (left pial synangiosis) with resolution of her choreiform movements and normalization of her gait. Our case demonstrates that moyamoya disease should be suspected when evaluating a child with hemichorea and describes resolution of symptoms after revascularization surgery. Neuroimaging and vascular studies should be obtained in children with unilateral movement disorder.
Keywords: moyamoya; unilateral chorea; movement disorder; hemichorea; pediatric; Caucasian